2016
DOI: 10.1024/0301-1526/a000507
|View full text |Cite
|
Sign up to set email alerts
|

Effects of rosuvastatin as an adjuvant treatment for deep vein thrombosis

Abstract: Summary:Background: Statins have been reported to help prevent the development and the recurrence of deep vein thrombosis (DVT). We conducted a prospective randomized clinical trial to compare the effects of rosuvastatin plus a low-molecular-weight heparin (LMWH), bemiparin, with conventional LMWH therapy in the treatment of DVT. Patients and methods: In total, 234 patients were randomized into two groups, 116 in the LMWH group and 118 in the statin plus LMWH group. All patients underwent lower limb duplex ult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 18 publications
0
17
0
3
Order By: Relevance
“…Moreover, the observation of accelerated thrombus resolution and less DVT-induced vein wall scarring suggested that statins protect against the onset of PTS [74]. Lastly, a clinical trial assessed the adjunction of rosuvastatin to the low-molecular-weight heparin (LMWH) bemiparin; after 3 months of follow-up, the CRP level and incidence of PTS were significantly lower in the patients receiving the adjunct statin treatment [76]. However, these preliminary results must be confirmed in large clinical trials.…”
Section: Anti-inflammatory Drugsmentioning
confidence: 99%
“…Moreover, the observation of accelerated thrombus resolution and less DVT-induced vein wall scarring suggested that statins protect against the onset of PTS [74]. Lastly, a clinical trial assessed the adjunction of rosuvastatin to the low-molecular-weight heparin (LMWH) bemiparin; after 3 months of follow-up, the CRP level and incidence of PTS were significantly lower in the patients receiving the adjunct statin treatment [76]. However, these preliminary results must be confirmed in large clinical trials.…”
Section: Anti-inflammatory Drugsmentioning
confidence: 99%
“…Within apolipoprotein E gene-deleted mice, hyperlipidemia resulted in a significantly elevated level of PAI-1 and an undetectable uPA concentration, so fibrinolysis and thrombus resolution were severely impaired [211]. Rosuvastatin has been shown to reduce these resolution-impairing effects in both mice and trial populations of human patients [212,213].…”
Section: Fibrinolysismentioning
confidence: 99%
“…The longer the thrombus is adjacent to the vessel wall, the higher the risk of vein wall damage. Fast removal of the thrombus may therefore prevent PTS …”
Section: Thrombus Resolutionmentioning
confidence: 99%